Frequencies of IL10 SNP genotypes by multiplex PCR-SSP and their association with viral load and CD4 counts in HIV-1-infected thais - Doungnapa Kingkeow (2018)
Background: Interleukin (IL)-10 is an immunoregulatorycytokine, levels of which can beinfluenced by single nucleotide polymorphisms(SNPs) in the promoter. Some, but not allprevious studies have shown associations ofIL10 SNPs with HIV-1 disease progression,using markers such as viral load or CD4 count.There are few data on IL10 SNP frequenciesand HIV-1 disease in regions where non-BHIV-1 subtypes predominate.Objective: To determine genotypes, haplotypes,allele frequencies and associations withmarkers of HIV-1 disease progression of IL10SNPs.Methods: A new multiplexed PCR-SSP assayto detect IL10 SNPs at positions -1082, -819and -592 was developed and used to determinegenotypes and haplotypes in 244 HIV-1CRF01_AE-infected northern Thais having amedian time since HIV-1 infection of 2.7 years.Results: At position -1082 of IL10, AA genotypeand A allele were the most common (87.3%and 93.2%, respectively). The -819 CT and-592 CA genotypes were the most prevalent(44.3%), and -819T and -592A were the mostprevalent alleles (64.8%). The ATA/ATA wasthe most common genotype (42.6%) with themost prevalent haplotype of ATA (64.7%). Noassociations of any of the three IL10 SNPs withCD4+ or CD8+ T cell counts or with viral loadwere found.Conclusions: This first report of IL10-1082A,-819T and the IL10-592A allele frequencies inHIV-1-infected Thais shows the highestfrequencies in HIV-1-infected personsworldwide. The lack of association of IL10SNPs with CD4+ T cell count and viral loadsuggest that other genes may influence these markers in HIV-1-infected Thais.